The Unique Role of Hope and Optimism in the Relationship between Environmental Quality and Life Satisfaction during COVID-19 Pandemic - Wider, Walton; Nasehah, Mohd Taib; Mohd Wafiy Akmal, Ahmad Khadri; Yip, Foon Yee; Surianti, Lajuma (Molecular Diversity Preservation International (MDPI), 2022)
COVID-19 in Malaysia has significantly affected the higher education system of the country and increased the level of distress among university students. Empirical evidence proposed that environment quality is associated with university students’ life satisfaction during COVID-19. It was found that hope and optimism are linked with greater life satisfaction in general. Although past literature has reported the effects of hope and optimism on life satisfaction, there are limited studies examining the underlying mechanism among Malaysian private university students. Therefore, the current study offers the preliminary understanding of the intervening role of hope and optimism on the relationship between environmental quality and life satisfaction among private university students in Malaysia. A total of 133 private university students in Malaysia were recruited through homogenous convenience sampling. Partial least square structure equation modeling (SmartPLS) was used to analyze the mediation models. The results revealed that only hope mediated the relationship between environmental quality and life satisfaction, but not optimism. Hence, it is proposed that mental health providers should focus on providing hope-related interventions to university students in confronting COVID-19 challenges and ultimately improving life satisfaction.